Impact of solids residence time on biological nutrient removal performance of membrane bioreactor - Ersu, Cagatayhan Bekir; Ong, Say Kee; Arslankaya, Ertan; Lee, Yong-Woo (PERGAMON-ELSEVIER SCIENCE LTD, 2010)
Impact of long solids residence times (SRTs) on nutrient removal was investigated using a submerged plate-frame membrane bioreactor with anaerobic and anoxic tanks. The system was operated at 10, 25, 50 and 75 days SRTs with hydraulic retention times (HRTs) of 2 h each for the anaerobic and anoxic tanks and 8 h for the oxic tank. Recirculation of oxic tank mixed liquor into the anaerobic tank and permeate into the anoxic tank were fixed at 100% each of the influent flow. For all SRTs, percent removals of soluble chemical oxygen demand were more than 93% and nitrification was more than 98.5% but total nitrogen percent removal seemed to peak at 81% at 50 days SRT while total phosphorus (TP) percent removal showed a deterioration from approximately 80% at 50 days SRT to 60% at 75 days SRT. Before calibrating the Biowin (R) model to the experimental data, a sensitivity analysis of the model was conducted which indicated that heterotrophic anoxic yield, anaerobic hydrolysis factors of heterotrophs, heterotrophic hydrolysis, oxic endogenous decay rate for heterotrophs and oxic endogenous decay rate of PAOs had the most impact on predicted effluent TP concentration. The final values of kinetic parameters obtained in the calibration seemed to imply that nitrogen and phosphorus removal increased with SRT due to an increase in anoxic and anaerobic hydrolysis factors up to 50 days SRT but beyond that removal of phosphorus deteriorated due to high oxic endogenous decay rates. This indirectly imply that the decrease in phosphorus removal at 75 days SRT may be due to an increase in lysis of microbial cells at high SRTs along with the low food/microorganisms ratio as a result of high suspended solids in the oxic tank. Several polynomial correlations relating the various calibrated kinetic parameters with SRTs were derived. The Biowin (R) model and the kinetic parameters predicted by the polynomial correlations were verified and found to predict well the effluent water quality of the MBR at 35 days SRT. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Nitrification; Denitrification; Phosphorus uptake; SRT; Modeling; WASTE-WATER TREATMENT; ACTIVATED-SLUDGE SYSTEM; CONFIGURATIONS; MBR; Engineering; Environmental Sciences & Ecology; Water Resources